IGCSE Accounting - Coucom, Catherine (Cambridge University Press, 2002)
Accounting: IGCSE provides comprehensive coverage of the CIE syllabus (0452). Designed for classroom learning, it also encourages self-assessment and independent thinking. Its student friendly approach makes this ideal for students studying the IGCSE examination.